PERAN COUNTRY OF ORIGIN PADA PEMBENTUKAN BRAND EQUITY - Ariningsih, Endah Pri; Ekowati, Titin; Budiyanto, Budiyanto (Universitas Muhammadiyah Magelang, 2019)
Various variations mobile phone brands that enter the Indonesian market, consumers provides many alternatives to choose the products that best suit their needs. But on the other hand it can make consumers experience difficulties in making choices on the products they will buy. Marketers must be observant to see exactly what makes consumers interested in making purchases on handphone products. At present there are many mobile brands from China that have entered Indonesia and are in great demand by consumers in our country. Even though many years ago many considered Chinese-made products to be of poor quality In this study the researcher wanted to know how the role of the country of origin to be treated using three different countries using the COM difference was seen as the impact on the brand equity of the product. Research will be conducted using experimental design using 6 factors. The analysis tool that will be used in this study is different testing using One Ways ANOVA. The results showed that there were only one of the six groups which proved to be significantly different between before and after the treatment. While the results of testing the impact of providing information proved that COO had an effect on brand equity for two products.